An Advanced Bioreactor Simulating Dynamic Physiological Conditions in the Human Ascending Colon: MimiCol3 - Regine Beeck; Annemarie Dols; Felix Schneider; Dariah-Sohreh Seradj; Julius Krause; Philipp Schick; Werner Weitschies (MDPI AG, 2022)
In recent years, the colon has become a hot topic in biopharmaceutical research as several in vitro models of the human colon have been presented. A major focus is on the characterization of the microbiota and its capabilities. The aim of the present study was to further develop the MimiCol, preserving its properties and accelerating data acquisition. Emphasis was placed on the simplicity of its design and easy scalability. To prove the viability of the concept, degradation of sulfasalazine was investigated, and the bacterial composition during the experiment was assessed by 16S rRNA sequencing. The transfer of the experimental conditions to the new model was successful. Commercially available components were implemented in the setup. The model MimiCol3 represented the colon ascendens satisfactorily in its properties regarding volume, pH value, and redox potential. 16S rRNA sequencing led to further insights into the bacterial composition in the vessels. Degradation of sulfasalazine was in good agreement with in vivo data. The new model of the colon ascendens MimiCol3 enabled us to collect more reliable data, as three experiments were conducted simultaneously under the same conditions.